Numerical Solution of the Viscous Flow Past a Circular Cylinder Under the Influence of a Magnetic Field - Morzyński, M.; Gürgey, E.; Thiele, F. (Engineering Transactions, 1997)
The steady laminar incompressible viscous flow over an insulated circular cylinder is investigated. The flow is subjected to an external uniform magnetic field. Besides the familiar Reynolds number, the flow structure also depends on the Hartmann number. A fully implicit finite difference method based on the stream function formulation of the Navier-Stokes equations is used to solve the problem numerically. The magnetic field has a significant influence on the flow, it can delay or even completely cancel the development of the wake and the separation. The flow tends to be more stable since the convection process is suppressed by the magnetic field. Furthermore the drag is increased although the separation is absent.